2012
DOI: 10.5194/acp-12-9365-2012
|View full text |Cite
|
Sign up to set email alerts
|

The challenge to NO<sub>x</sub> emission control for heavy-duty diesel vehicles in China

Abstract: Abstract. China's new "Twelfth Five-Year Plan" set a target for total NO x emission reduction of 10 % for the period of 2011-2015. Heavy-duty diesel vehicles (HDDVs) have been considered a major contributor to NO x emissions in China. Beijing initiated a comprehensive vehicle test program in 2008. This program included a sub-task for measuring onroad emission profiles of hundreds of HDDVs using portable emission measurement systems (PEMS). The major finding is that neither the on-road distance-specific (g km −… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(70 citation statements)
references
References 32 publications
6
62
0
Order By: Relevance
“…Emission NO 2 /NOx ratios in biomass burning are, for a variety of fuels, in the 0.1-0.3 range [40,45]. These values are larger than those arising from vehicles, the most important NOx source in large cities [46]. During the year 2006 at the monitoring station in Wuppertal (Germany), an annual average NO 2 /NOx emission ratio of 0.12˘0.01 was reported by Kurtenbach et al, [47].…”
Section: Discussionmentioning
confidence: 94%
“…Emission NO 2 /NOx ratios in biomass burning are, for a variety of fuels, in the 0.1-0.3 range [40,45]. These values are larger than those arising from vehicles, the most important NOx source in large cities [46]. During the year 2006 at the monitoring station in Wuppertal (Germany), an annual average NO 2 /NOx emission ratio of 0.12˘0.01 was reported by Kurtenbach et al, [47].…”
Section: Discussionmentioning
confidence: 94%
“…suggested that current emission standard implemented in Beijing (Euro IEuro IV) and nationwide might have limited impacts on reducing NO x emissions. Wu et al (2012) found the NO x emission factors for heavy-duty diesel buses did not improve in most cases as emission standards became more stringent, and that the average NO x emission factors of Euro II, Euro III and Euro IV buses in Beijing under the same typical driving cycle were all around 12 g km −1 . These findings are consistent with earlier work of Velders et al (2011) for Europe as well as Huo et al (2012b) for China, where similar noncompliance was identified.…”
Section: Failure In the Control Of Heavy Diesel Vehiclesmentioning
confidence: 99%
“…The local emission factors were collected from a mass of measuring data from the Tsinghua University and China Automotive Technology & Research Center, such as bench testing and on-road vehicle emissions measurements in Beijing (Huo et al, 2009;Hu et al, 2012;Wu et al, 2012;. Meanwhile, the fuel consumption factors for vehicles were measured and included in this model.…”
Section: Emission Factorsmentioning
confidence: 99%
“…The average vehicle running speed is one of the important Figure 1. Emission factors of NO x , HC, CO, PM and fuel consumption factors of gasoline and diesel (Huo et al, 2009;Hu et al, 2012;Wu et al, 2012; parameters of traffic data and is utilized to estimate traffic flow.…”
Section: Average Running Speed Based On Floating Car Datamentioning
confidence: 99%